Der elektronische Raum : 15 Positionen zur Medienkunst. - Cornwell, Regine; Denk, Andreas; Dinkle, Söke; Donga, Thomas; Dunn, David; Edith-Decker-Philips; Felstau, Michael; Good, Paul; Goodman, Cynthia; Goodrow, Gérard, A.; Huemer, Markus; Huhtamo, Erkki; et al. (Bonn : Kunst- und Ausstellungshalle der Bundesrepublik Deutschland, 1998)
Petry, Michael ; Vasulka, Woody ; Scott, Jill ; Odenbach, Marcel ; Hegedüs, Agnes ; Daegen, Dismar ; Hoover, Nan ; Bruch, Klaus vom ; Weinbren, Grahame ; Mignonneau, Laurent ; Sommerer, Christa ; Seaman, Bill ; Azzuro, Studio ; Rosenbach, Ulrike ; Shaw, Jeffrey ; Friedmann, Robert ; Hill, Gary
Duits
boek